(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
It is a difficult task to balance societal need for development and the need to sustain the environment as a life supporting system of the planet. Engineers and scientists have accept the current and future challenges in order to ensure the sustainability of both the environment and the society. Two major changes are needed in the training and practices of scientists and engineers. First, the need to adopt advanced technologies as the basic knowledge platform in solving environmental related problems. Second, the need to understand and embrace multi-, inter- and trans-disciplinary approaches in solving current and future problems. Most important of all, the solutions provided must not only be feasible from the technological and economics point of view but it must also address the psychological and emotional well-being of the society.